Printable and Stretchable Giant Magnetoresistive Sensors for Highly Compliant and Skin‐Conformal Electronics. Issue 12 (2nd February 2021) - Ha, Minjeong; Cañón Bermúdez, Gilbert Santiago; Kosub, Tobias; Mönch, Ingolf; Zabila, Yevhen; Oliveros Mata, Eduardo Sergio; Illing, Rico; Wang, Yakun; Fassbender, Jürgen; Makarov, Denys
Abstract: Highly compliant electronics, naturally conforming to human skin, represent a paradigm shift in the interplay with the surroundings. Solution‐processable printing technologies are yet to be developed to comply with requirements to mechanical conformability of on‐skin appliances. Here, it is demonstrated that high‐performance spintronic elements can be printed on ultrathin 3 µm thick polymeric foils enabling the mechanically imperceptible printed magnetoelectronics, which can adapt to the periodic buckling surface to be biaxially stretched over 100%. They constitute the first example of printed and stretchable giant magnetoresistive sensors, revealing 2 orders of magnitude improvements in mechanical stability and sensitivity at small magnetic fields, compared to the state‐of‐the‐art printed magnetoelectronics. The key enabler of this performance enhancement is the use of elastomeric triblock copolymers as a binder for the magnetosensitive paste. Even when bent to a radius of 16 µm, the sensors printed on ultrathin foils remain intact and possess unmatched sensitivity for printed magnetoelectronics of 3 T ‐1 in a low magnetic field of 0.88 mT. The compliant printed sensors can be used as components of on‐skin interactive electronics as it is demonstrated with a touchless control of virtual objects including zooming in and out of interactive maps and scrolling through electronic documents. Abstract : Highly compliant and printable giant magnetoresistive sensors reveal skin‐conformability and excellent sensitivity to small magnetic fields because of highly sensitive giant magnetoresistive multilayers bound with sticky triblock copolymer, which is capable of on‐skin interactive electronics for a touchless control of virtual objects.